Harmonic decomposition of two particle angular correlations in Pb-Pb collisions at √ˢɴɴ=2.76TeV - Aamodt, K.; Abelev, B.; Abrahantes Quintana, A.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; et al. (Elsevier, 2012)
Angular correlations between unidentified charged trigger (t) and associated (a) particles are mea- sured by the ALICE experiment in Pb–Pb collisions at √ˢɴɴ = 2.76 TeV for transverse momento 0.25 < Pᴛᵗʹᵃ < 15 GeV/c, where Pᵗᴛ > Pᵃᴛ . The shapes of the pair correlation distributions are studied in a variety of collision centrality classes between 0 and 50% of the total hadronic cross section for particles in the pseudorapidity interval |η| < 1.0. Distributions in relative azimuth Δφ ≡ φᵗ − φᵅ are analyzed for |Δη| ≡ | ηᵗ − ηᵅ| > 0.8, and are referred to as “long-range correlations”. Fourier components VnΔ ≡ 〈 cos(nΔφ)〉 are extracted from the long-range azimuthal correlation functions. If particle pairs are correlated to one another through their individual correlation to a common symmetry plane, then the pair anisotropy VnΔ(Pᵗᴛ , Pᵃᴛ) is fully described in terms of single-particle anisotropies vn(Pᴛ) as VnΔ(Pᵗᴛ, Pᵃᴛ) = vn(Pᵗᴛ)vn(Pᵃᴛ). This expectation is tested for 1< n <5 by applying a global fit of all VnΔ(Pᵗᴛ, Pᵃᴛ) to obtain the best values vn{GF}( Pᴛ). It is found that for 2< n <5, the fit agrees well with data up to paT ∼ 3–4 GeV/c, with a trend of increasing deviation as Pᵗᴛ and Pᵃᴛ are increased or as collisions become more peripheral. This suggests that no pair correlation harmonic can be described over the full 0.25 < Pᴛ < 15 GeV/c range using a single vn(Pᴛ) curve; such a description is however approximately possible for 2 <n <5 when Pᵃᴛ < 4 GeV /c. For the n = 1 harmonic, however, a single v¹(Pᴛ) curve is not obtained even within the reduced range Pᵃᴛ < 4 GeV /c.
Keywords: Ultra-relativistic heavy-ion collisions; Pb–Pb collisions; https://purl.org/pe-repo/ocde/ford#1.03.00